Spontaneous Bilateral Tubal Ectopic Pregnancy in a Low-Risk Patient: A Case Report with Implications for Preoperative Patient Counseling - Josephine Eva Gathura; Amro Elfeky; Rodney McLaren; David Herzog; Richard Grazi (Case Reports in Obstetrics and Gynecology)
Bilateral tubal ectopic pregnancies (BTP) are the rarest form of ectopic pregnancy. They are difficult to diagnose preoperatively, and an evidence-based guideline for management does not exist. In this report, we discuss a 35-year-old patient who presented with suspected right tubal ectopic pregnancy. BTP was diagnosed intraoperatively, and a laparoscopic bilateral salpingectomy was performed without complication. The diagnosis was subsequently confirmed by pathology. This case highlights the importance of patient counseling and comprehensive preoperative planning. Due to the poor presurgical diagnosis of BTP, patient counseling should include the possibility of BTP, appropriate options for management, and potential loss of fertility following treatment. In addition, all cases of suspected ectopic pregnancy necessitate a thorough preoperative investigation of bilateral adnexa and intraoperative inspection of the pelvis.